Root-ception

Algebra Level 2

Find the answer of 5 + 2 ( 9 + 6 2 3 ) 2 \sqrt { 5+2\left( \sqrt { 9+6\sqrt { 2 } } -\sqrt { 3 } \right) } -\sqrt { 2 }

Note : ( a + b ) 2 = a 2 + 2 a b + b 2 { \left( a+b \right) }^{ 2 }={ a }^{ 2 }+2ab+{ b }^{ 2 }

6 \sqrt { 6 } 3 -\sqrt { 3 } 6 -\sqrt { 6 } 3 \sqrt { 3 }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chan Lye Lee
Nov 1, 2015

Note that 9 + 6 2 = 3 ( 3 + 2 2 ) = 3 ( 2 + 1 ) 2 9+6\sqrt{2} = 3\left(3+2\sqrt{2}\right)=3\left(\sqrt{2} +1\right)^2 . Hence, 9 + 6 2 = 3 ( 2 + 1 ) \sqrt{9+6\sqrt{2}}=\sqrt{3} \left(\sqrt{2} +1\right) and so 9 + 6 2 3 = 3 2 \sqrt{9+6\sqrt{2}} -\sqrt{3}=\sqrt{3} \sqrt{2} .

Next, 5 + 2 3 2 = ( 2 + 3 ) 2 5+2\sqrt{3} \sqrt{2} = \left(\sqrt{2} +\sqrt{3}\right)^2 . Hence, 5 + 2 3 2 = 2 + 3 \sqrt{5+2\sqrt{3} \sqrt{2}} = \sqrt{2} +\sqrt{3} and so 5 + 2 ( 9 + 6 2 3 ) 2 = 3 \sqrt { 5+2\left( \sqrt { 9+6\sqrt { 2 } } -\sqrt { 3 } \right) } -\sqrt { 2 } = \sqrt{3} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...